Biofilm forming potential and antimicrobial susceptibility of newly emerged Western Australian Bordetella pertussis clinical isolates - Dorji, D.; Graham, Ross; Richmond, P.; Keil, A.; Mukkur, T. (2016)
Whooping cough caused by Bordetella pertussis is increasing in several countries despite high vaccine coverage. One potential reason for the resurgence is the emergence of genetic variants of the bacterium. Biofilm formation has recently been associated with the pathogenesis of B. pertussis. Biofilm formation of 21 Western Australian B. pertussis clinical isolates was investigated. All isolates formed thicker biofilms than the reference vaccine strain Tohama I while retaining susceptibility to ampicillin, erythromycin, azithromycin and streptomycin. When two biofilm-forming clinical isolates were compared with Tohama I, minimum bactericidal concentrations of antimicrobial agents increased. Isobaric tags for relative and absolute quantitation (iTRAQ)-based proteomic analysis revealed significant differences in protein expression in B. pertussis biofilms, providing an opportunity for identification of novel biofilm-associated antigens for incorporation in current pertussis vaccines to improve their protective efficacy. The study also highlights the importance of determining antibiograms for biofilms to formulate improved antimicrobial therapeutic regimens.